Internal marketing as a direction to develop creativity in the organization - bourenane, Brahim; bourenane, Fatima zohra; bouameur, aicha (Journal of Excellence for Economics and Management Research, 2022)
The human component has been and remains the most important asset of the enterprise and its interest in it is an imperative imposed by competition. as its modern concept gives a marketing quality to the management of the human resource by considering all workers as clients who are targeted to suit their material and moral needs.In view of the importance of addressing the concept of internal marketing from a managerial point of view, the study aims to learn about its contribution to the development of creativity for employees in the enterprise, by addressing the most important concepts of internal marketing and creativity in the enterprise and the most important internal marketing procedures that contribute to this The article concluded that internal marketing methods of training, communication and motivation have an important role to play in the development and promotion of creativity in the enterprise, which requires the great interest of institutions in this important element – internal marketing – which contributes to the development of creativity that leads the Foundation for advancement and leadership.